Reliable and Traceable Temperature Measurements Using Thermocouples : Key to ensuring process efficiency and product consistency. Issue 1 (12th January 2023) - Edler, Frank
Temperature is the most frequently measured process variable in almost all industrial sectors from the chemical industry to glass and ceramics, refrigeration and power generation. During many manufacturing processes, continuous temperature control is an important part of product quality assurance and a matter of avoiding malfunctions or detecting them at an early stage. Measuring points can be located at different places such as in containers, pipe systems, machines, ovens or reactors, whereby different gaseous, liquid or solid media, for instance, steam, water, oil or special chemical substances may be involved. In view of these extremely complex tasks, flexibility is one of the most important requirements for measurement technology and signal processing. And this is where thermocouples, which can be adapted to almost all measuring tasks due to their simple design, become relevant. The basic design and operating principle of thermocouples are described in this paper; issues relating to calibration, traceability and measurement uncertainty are addressed. Recent developments to improve temperature measurement with thermocouples are presented. New, drift-optimised thermocouples, novel designs and alternative calibration methods are described, and their advantages over conventional thermocouples or calibration methods are specified.